Saving Habits Generasi Millenial: Self Control, Parental Socialization, dan Peer Influence di Kota Makassar - Rafiuddin, Fifriani; Parmitasari, Rika Dwi Ayu; Rusnawati (Study of Scientific and Behavioral Management, 2022)
Saving is one of the important things for individuals in financial management. The importance of saving, especially in the younger generation, affects financial well-being and satisfaction. This study aims to examine the effect of self control, parental and peer influence on saving habits. This research is a quantitative research. The population in this study was the entire millennial generation in Makassar City, with a sample of 202 respondents who met the predetermined criteria. The sampling technique used in this study was non-probability sampling. The results showed that self control, parental socialization and peer influence simultaneously had a significant effect on saving habits. Partially, the control (X1) and parental socialization (X2) have a significant positive effect on saving habits (Y), while the peer influence (X3) has no significant effect on saving habits (Y).